iPads in the Classroom - New Technologies, Old Issues: Are they worth the effort? - Reid, D.; Ostashewski, Nathaniel (AACE, 2011)
This paper presents the results of a research project that involved introducing iPads into twoelementary school classrooms to support the development of student digital storytelling skills. This was done because the school jurisdiction wanted to implement technology into grade six classrooms and provide useful support to the teachers and students. This project resulted in many positive learning experiences with the technology, with storytelling and across other components of the curriculum and the community. There are a number of implications of this research, including examining the constructionist theories underpinning the learning behind the creation of educational artifacts. In practice, there are many management issues regarding implementing new technology in classrooms as well as the pedagogical implications of giving students access to technology that can allow them to create their own understandings in classrooms.